PENGARUH REMUNERASI, PENGUKURAN KINERJA, DAN ANALISIS JABATAN TERHADAP KUALITAS MUTU PEKERJAAN PEGAWAI DI BIRO KEUANGAN UNIVERSITAS NEGERI JAKARTA TAHUN 2022 - Pamungkas, Sigit Putro; Sukiman, Sukiman; Budianto, Irawab R.d; Madiistriyatno, Harries (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
Nowadays, people are increasingly smart and aware of getting quality products or services. People are very intelligent and understand about quality products or services. For this reason, an institution is required to provide quality products or services to provide satisfaction to consumers. Providing quality products or services, of course, cannot be separated from the extent of human resources (HR) owned by an institution. The reason is, through quality human resources, quality products or services will of course be produced. In the midst of increasingly tight business competition like today, improving the quality of employees is one of the important things for an institution. Because, the quality of products and services is largely determined by technology, systems, work methods and personal integrity to contribute the best quality work. Several factors that influence the quality of employee work are 1. Remuneration is a component that can increase employee motivation. With appropriate remuneration, an employee will work at his best. In this way, remuneration is something that can influence employee productivity and work performance; 2. Performance measurement is a process of assessing work progress against predetermined goals and objectives, including information on the efficiency of resource use in producing goods and services; 3. Job Analysis is a systematic process that aims to find out about the main points of the position which consists of several tasks, jobs, authority and responsibilities, as well as about the qualification provisions for the things sought such as experience, expertise, ability, education so that they can carry out their duties well in their position.